Spatiotemporal Variation of Drought and Its Correlation With Plant Species of Yunnan Province, China - Xu, Xinhui; Zhou, Xingyu; Liu , Zhenqiang; Zhao, Xiaoqing (Bangladesh Journal of Botany, 2021)
Drought is the main natural disaster in Yunnan Province, China. In the present paper monthly precipitation observation data from Yunnan Province durign the period of 1966 - 2015 were used. From the data, the selected percentage of precipitation anomalies was used as drought index. By applying the ArcGIS inverse distance interpolation method and Mann Kendall non parametric trend test method the spatiotemporal variation characteristics of drought in Yunnan province were analyzed. Results show that the drought in Yunnan Province has a slightly upward trend. In spring and winter, there is a tendency to become wet but in summer and autumn, the tendency is shown by dry condition. It was observed that the studied area is prone to a severe drought in winter, and there will be more droughts in the east part, the northwest part, and the southwest part of Yunnan province when it is autumn. In other periods, severe doughts usually attack the middle part of Yunnan province, which can be proved by the characteristics of vegetation distribution. Bangladesh J. Bot. 50(4): 1133-1142, 2021 (December)